PENGARUH INOVASI PRODUK DAN PERSEPSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN KARTU TELKOMSEL PADA GRAI TELKOMSEL LAHAT (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
The data collection method used in this research is a literature study, namely the method used to obtain theoretical data related to the problems discussed. Then field studies are interviews, observations, related to the problem under study to obtain clear data. The analytical method used in this study is a qualitative comparison between existing theories and quantitative analysis, namely data analysis using multiple linear regression analysis, t test, F test, and coefficient of determination. Based on the results of research that has been carried out on consumers who make purchasing decisions at Grai Telkomsel Lahat, it shows the effect partially and simultaneously. The value of the coefficient of determination (r^2) is 0.723. This means that the influence of consumer purchasing decisions on Grai Telkomsel Lahat variables can be explained by product innovation variables and consumer perception variables with a contribution of 72.3%, while the remaining 27.7% can be explained by other variables.